Aktivitas Menonton Televisi Sebagai Aktivitas Sosial Di Antara Penghuni Kos - Saputri, Palupi Laras; , Nur Latifah Umi Satiti, M.A (2017)
Television-viewing is a complex media which influences human´s habits in everyday life. This research is aimed at understanding, how television-viewing habits can create social interactions within the comunity of a dormitory, and how it shapes intimacy through the activity of watching television together at. Content analysis method was used, through text collecting which consists cultural aspect by observing the case and doing an interview. Samples were collected by using purposive sampling method and iangulation as data validation. The research has shown that through watching television together, people can easily create interpersonal relations, however the viewers may be distracted by another activities, such as multitasking while in between. This research could be used as a further reference for research about television-viewing habits in the future.